Dual career (DC) experiences of Korean elite judokas before and at university - Hong, H. J.; Hong, S. H. (Psychology of Sport and Exercise, 2024)
The present study aims to explore the experiences of Korean elite judokas in managing dual career (DC) during: (a) pre-university years, (b) at the university, and (c) in preparation for the transition to the post-university life. We adopted an intrinsic case study design to gain a better understanding of the experiences of Korean elite judokas at a university. We aimed to explore a particular case in depth, focusing on the experiences of the individuals involved. Purposive sampling was applied to 12 DC athletes (seven male; five female) who are elite judokas and were in year 4 of university study at the time of the data collection. They studied at the same South Korean university and competed at an international level. Semi-structured interviews were used to collect data and thematic analysis was applied. The analysis identified four main themes: (a) DC path of prioritising sport and maintaining education, (b) Increasing sport demands and their impact on athletes` DCs, (c) Specific career development barriers of Korean judokas, (d) Coping resources and strategies and support in need. The study discusses the unique challenges and barriers as well as coping strategies of Korean judoka based on the Athletic Career Transition model, highlighting the importance of sociocultural context in their experiences.